British crime film : subverting the social order - Forshaw, Barry (Crime Files Series, 2012)
Presenting a social history of British crime film, this book focuses on the strategies used in order to address more radical notions surrounding class, politics, sex, delinquency, violence and censorship. Spanning post-war crime cinema to present-day "Mockney" productions, it contextualizes the films and identifies important and neglected works.